Composite Clayey Sand and Short Fiber - Chegenizadeh, Amin; Nikraz, Hamid (Trans Tech Publications Inc, 2012)
Composite soils have been widely used in civil engineering applications, especially in slopes, embankment dam and landfills. This paper aims to investigate effect of fiber inclusion on shear stress of composite soil (i.e. sand composite). A series of laboratory direct shear tests carried out to evaluate fiber effect on strength behavior of composite sand. Clayey sand was selected as soil part of the composite and glass fiber was used as reinforcement. The fiber parameters differed from one test to another, as fiber length were changed from 10 mm to 35 mm and fiber content were varied from 0.6% and 3%. Normal stress kept constant at 150 kpa. For each test, stress_displacement graph derived and the results were compared. The results proved that inclusion of fiber affected strength behaviour of sand composite so that increasing in fiber content and length caused increasing in shear stress.